Parasitofauna de ciclídeos ornamentais brasileiros oriundos de ambientes natural e de cativeiro. - Antonucci, Antonio Mataresio (2014)
Fishes are the most infected vertebrates due to their long evolutionary history. Moreover, the characteristics of the aquatic environment facilitate the propagation, the reproduction and the complementation of the parasites life cycle, generating high infestation rates in fishes. The composition of the fish parasite fauna depends on factors related to the environment (water quality, pH changes, ammonia concentrations, dissolved oxygen available, variations in temperature, water levels and seasonal effects), to the host (habitat, eating behavior, physiology, age, sex and immunology), to the parasite (availability of infective larvae and intermediate and / or definitive hosts) and the co-evolutionary history between fish and their parasites. And when one or more of these factors unbalance, illness occurs on the hosts. But in sudden exposures, as it occurs in cases of introduction of parasite species to an environment where the evolutionary history between parasite and host is short or non-existent, pathologies arise on most severe expressions. These biological characteristics are of prime importance for the development of aquaculture activities with commercial purposes. The ornamental fish farming is one of the most lucrative branches of world fish production, comprising both fishes raised on specialized farms and fishes from the extractive fishing. The Brazilian ichthyofauna has fish shape and coloration much appreciated by both national and international market as is the case of Astronotus ocellatus(Apaiari), A. crassipinnis (Apaiari), Pterophyllum scalare (Acará-bandeira) and Symphysodon aequifasciatus (Acará-disco) which are heavily fished, but are also bred on a commercial scale due to the existence of specialized technological packages. However, the sanitary issue involving these animals is not quite elucidated, existing a knowledge gap on the parasites that affect these species both in natural environment and in breeding; there is also no knowledge about the ways of controlling the pathogens that affect the environment in captivity. The objective of this thesis was to increase the knowledge about the parasite fauna of Brazilian ornamental fish species A. crassipinnis, A. ocellatus, P. scalare and S. aequifasciatus, as well as possible forms to control parasitic infestations on these fish.